Three cups of tea : one man's mission to promote peace -- one school at a time - Mortenson, Greg.; Relin, David Oliver (New York : Penguin Books, 2007)
One man's campaign to build schools in the most dangerous, remote, and anti-American reaches of Asia: in 1993 Greg Mortenson was an American mountain-climbing bum wandering emaciated and lost through Pakistan's Karakoram. After he was taken in and nursed back to health by the people of a Pakistani village, he promised to return one day and build them a school. From that rash, earnest promise grew one of the most incredible humanitarian campaigns of our time--Mortenson's one-man mission to counteract extremism by building schools, especially for girls, throughout the breeding ground of the Taliban. In a region where Americans are often feared and hated, he has survived kidnapping, death threats, and wrenching separations from his wife and children. But his success speaks for itself--at last count, his Central Asia Institute had built fifty-five schools.--From publisher description.
In Mr. Mortenson's orbit -- Failure -- The wrong side of the river -- "Progress and perfection" -- Self-storage -- 580 letters, one check -- Rawalpindi's rooftops at dusk -- Hard way home -- Beaten by the braldu -- The people have spoken -- Building bridges -- Six days -- Haji Ali's lesson -- "A smile should be more than a memory" -- Equilibrium -- Mortenson in motion -- Red velvet box -- Cherry trees in the sand -- Shrouded figure -- A village called New York -- Tea with the Taliban -- Rumsfeld's shoes -- "The enemy is ignorance" -- Stones into schools.
Originally published in the USA by Viking Penguin, 2006.
Includes index.
Keywords: Girls' schools -- Pakistan; Girls' schools -- Afghanistan; Humanitarian assistance, American -- Pakistan; Humanitarian assistance, American -- Afghanistan; Mortenson, Greg